Implications of Public Trust Due to Weak Law Enforcement Morality - Eka Sakti Koeswanto; Riswandi Riswandi; Ahmad Redi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Law enforcement has a strategic role in determining the quality of law enforcement in a country. In Indonesia, the performance of law enforcers is often considered unsatisfactory. This public dissatisfaction is a sign of weak law enforcement in Indonesia. The law which is considered a way to seek justice for society gives a sense of injustice. One of the causes of weak law enforcement in Indonesia is the quality of law enforcement. The low level of morality results in a lack of professionalism and unwillingness to enforce law enforcement. This morality is also related to corruption by law enforcement officers (judicial corruption). Law enforcers who are supposed to enforce the law are involved in corrupt practices. This low mortality causes law enforcement in Indonesia to be weak. Law enforcement will be strong and respected if law enforcers act professionally, and honestly and apply the principles of good governance. One example of weak law enforcement fines for drivers who violate traffic rules. Not a few motorists who do not want to be tried in court and choose the "peaceful place" route. This has been happening for years so it has become an open secret. As a result, there is public distrust of law enforcement. If not resolved immediately, this public distrust can lead to vigilante action. People who don't trust law enforcement may prefer to solve problems with violence or their way. A legal expert Leon Duguit said that the law is a rule of public behavior that must be obeyed as a guarantee of the common interest, which if violated will lead to criticism as a reaction. Meanwhile, law enforcement is a system in which there is a government or state institution that acts in an organized manner to ensure justice and order by using instruments or tools of power.